7P Marketing Mix Priorities in Agricultural Inputs: A Comparative AHP Study of MNC and National/Local Firms - Muh. Nur Alif Rapi; Ujang Sumarwan; Joko Purwono (Riviera Publishing, 2026)
The agricultural input industry faces increasingly complex competition between multinational corporations (MNCs) and national/local firms. Differences in resources, technological capability, distribution networks, and market proximity imply that marketing strategies cannot be standardized across firm types. This study aims to analyze the priorities of the 7P marketing mix in the agricultural input industry and compare the priority patterns between MNC and national/local firms. The study employed the Analytical Hierarchy Process (AHP) involving 12 expert panelists from industry practitioners, academics, and agribusiness experts. The results show that MNC firms prioritize Product (0.234), People (0.165), and Promotion (0.163), whereas national/local firms prioritize Product (0.193), People (0.177), Price (0.167), and Promotion (0.149). The main sub-criteria for MNC firms are dominated by product innovation, brand reputation, core product quality, professionalism, and price-value alignment. In contrast, national/local firms emphasize field staff competence, direct communication through demonstration plots, core product quality, competitive pricing, and the quality of demonstration plots. These findings indicate that MNC firms rely more on product differentiation and reputation, whereas national/local firms depend more on field proximity, pricing, distribution, and tangible evidence of product performance. Artificial Intelligence serves as an enabler of marketing strategy implementation rather than as a primary priority.